Gold(I)-Catalyzed Iodination of Arenes - Leboeuf, David; Ciesielski, Jennifer; Frontier, Alison J. (Synlett, 2014)
A wide variety of electron-rich arenes were efficiently converted into the corresponding iodinated compounds via a gold(I)-catalyzed reaction under mild conditions.
Keywords: gold; homogeneous catalysis; iodination; arenes; electrophilic aromatic substitution